Politics and International Relations. Issue 4 (3rd July 2020) - Simon, Steven
Abstract : Shields of the Republic: The Triumph and Peril of America's Alliances Mira Rapp-Hooper. Cambridge, MA: Harvard University Press, 2020. £22.95/27.95. 272 pp. Holding the Line: Inside Trump's Pentagon with Secretary Mattis Guy M. Snodgrass. New York: Sentinel, 2019. 27.00. 352 pp. A State at Any Cost: The Life of David Ben-Gurion Tom Segev. Haim Watzman, trans. New York: Farrar, Straus and Giroux, 2019. £30.00/40.00. 816 pp. How the West Stole Democracy from the Arabs: The Syrian Arab Congress of 1920 and the Destruction of Its Historic Liberal–Islamic Alliance Elizabeth F. Thompson. New York: Atlantic Monthly Press, 2020. 30.00. 496 pp. The Inevitability of Tragedy: Henry Kissinger and His World Barry Gewen. New York: W. W. Norton, 2020. 30.00. 480 pp.